Agricultural price policy in the Republic of South Africa, the Southern African Customs Union, and food security in Botswana - Roland Herrmann; John Cathie (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
This analysis is concerned with the direct impacts of the regulation of food markets under SACU on food security in the BLS countries. There are two basic rules in SACU determining trade in food and non-food products (Ettinger, 1974; Maasdorp, 1986). The first of these is that common tariffs exist for trade with the rest of the world. The second is that the internal market of SACU represents a free-trade area. The common external tariffs of SACU are fixed by the Republic of South Africa. These rules of SACU link the agricultural price policy in the Republic of South Africa with food imports and food security in the BLS countries. It is the objective of this paper to investigate this linkage which has been hitherto ignored in the literature. The paper analyzes quantitatively how the agricultural policy of the Republic of South Africa affects food security in Botswana and particularly how this was transmitted via the rules of SACU during the period 1969-84. The analysis begins by describing the institutional relationship between agricultural price policy in South Africa and food security in the BLS countries. Section 3 considers empirically what impacts agricultural policy in South Africa has had upon the food import sector of Botswana, and the magnitude, trends and instabilities of these economic variables are investigated. The analysis is based upon econometrically estimated food import demand equations for Botswana. Section 4 takes into consideration the effects of the customs union remittances received from SACU by Botswana. The effects of customs union membership, as they apply to food security in Botswana are tested by the hypothesis as to whether the joint impact of the external tariff policy on food and of customs union revenues was positive or negative. Finally, in section 5 the main results of the analysis are summarized and suggestions for further research are indicated.
Keywords: 330; Agrarmarktordnung; Südafrika